Gratification In Promotion In View Of The Law - Hasbi, Mhd. (Legalpreneur Journal, 2023)
AbstractMany cases of corruption by state officials are increasingly systematic and widespread, one of which is the existence of gratification. Therefore, gratuity should have its own meaning inthe law if the definition or understanding of gratuity has not been included in the generalprovisions, it will be very likely that there will be ambiguity in the interpretation of thecriminal act of gratuity. In Article 12 B Of The Corruption Eradication Act No. 20 of 2001that a gift that is related to his position and contrary to his obligations or duties isconsidered an act that has an indication of gratuity. Legal norms in this article raises theambiguity of the norm (Vague Norm), the juridical indication that someone has done thecrime of gratuity is not clear, because the definition of gratuity itself is not written in thelegislation so that Article 12 B still needs to be touched to be seen clearly.Keywords: Legal, Law, Gratification